The Impact of Traditional Silvopastoral System on the Mixed Ombrophilous Forest Remnants - Pinotti,Lígia Carolina Alcântara (2018)
ABSTRACT The results of an evaluation of the impact of traditional silvopastoral system on floristic and phytosociology of the Mixed Ombrophilous Forest (MOF) remnants, named caívas, in the North Plateau of Santa Catarina, South of Brazil are shown here to contribute to a better understanding of the impact of human activities on natural environments,. There was significant heterogeneity in floristic and structural aspects among the remnants. They exhibited high floristic integrity, with the presence of species typically registered in MOF. On the other hand, the incidence of exotic species was inexpressive. The predominance of smaller plant individuals than expected for adults of the species, combined with the predominance of secondary and pioneer species indicate the occurrence of repeated disturbances over the years. It is urgent to identify technological alternatives to enable appropriate foraging and increase in livestock production, ensuring economic and social sustainability with less environmental impact.